Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1111/j.1365-2648.2005.03602.x
|View full text |Cite
|
Sign up to set email alerts
|

Women's experiences of fatigue in chronic illness

Abstract: It is vital for healthcare workers to give opportunities for women to talk about fatigue, validate their experiences and provide support with self-care. Healthcare workers are encouraged to challenge their own meanings and expectations surrounding a person's report of fatigue so that opportunities for therapeutic intervention can be facilitated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
59
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(64 citation statements)
references
References 29 publications
4
59
0
1
Order By: Relevance
“…Our findings resonate to a certain extent with findings of others (Piper, Lindsey, Dodd, 1987;Richardson, 1995;Krupp and Christidoulou, 2001;Kralik, Telford, Price et al 2005;Ameringer and Smith, 2011), however none of these studies offered relational dimensions between the themes or segregates nor mention tiredness or exhaustion as part of the conceptualisation. The ethnoscience approach was instrumental to advancing the conceptualisation of the progressive continuum of fatigue through utilising taxonomical displays where relationships between different levels (domains, segregates, sub-segregates) were featured.…”
Section: Discussionsupporting
confidence: 72%
“…Our findings resonate to a certain extent with findings of others (Piper, Lindsey, Dodd, 1987;Richardson, 1995;Krupp and Christidoulou, 2001;Kralik, Telford, Price et al 2005;Ameringer and Smith, 2011), however none of these studies offered relational dimensions between the themes or segregates nor mention tiredness or exhaustion as part of the conceptualisation. The ethnoscience approach was instrumental to advancing the conceptualisation of the progressive continuum of fatigue through utilising taxonomical displays where relationships between different levels (domains, segregates, sub-segregates) were featured.…”
Section: Discussionsupporting
confidence: 72%
“…Fatigue is a common problem in individuals with chronic illnesses and this subjective symptom worries the individuals. Healthcare professionals have to learn communication techniques to help individuals to express concerns about fatigue [38,39]. More research is needed to find the best way of treating fatigue in people with rheumatic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The cultural understandings and behaviours portrayed in the findings of Kralik (2002), Kralik et al (2005) and Richardson (2005) resemble the cultural ideologies and behaviours characterising salience of the confined and submitter identities, as well as the fortified and camouflager identity in this study. The lack of confidence and self-esteem associated with the confined and submitter identities led women to shape their behaviours in line with other"s expectations.…”
Section: Culture Gender and Chronic Illnessmentioning
confidence: 86%
“…It was found that women internalised cultural constructions of gender; they were expected to place the needs of others before their own, and to maintain the cleanliness and tidiness of their households. Women made every effort to meet these expectations to avoid being undervalued, which caused conflict, led women to question their self-worth, and was associated with periods where women perceived a lack of control over their lives, their bodies and their pain, and where they experienced overwhelming fatigue (Kralik, 2002;Kralik et al, 2005). In Richardson"s (2005) study, women presented themselves as "good housewives" despite their pain, in order to maintain a positive identity by continuing to undertake traditional female tasks.…”
Section: Culture Gender and Chronic Illnessmentioning
confidence: 99%